Methodology for Diagnostics of the Company Management and Technological Maturity - Olena Martynyuk (Montenegrin Journal of Economics, 2017)
Approaches to the measurement and assessment of the company technological maturity level and management maturity apart, formulated in scientific researches and practical recommendations, significantly differ according to their purpose, content and depth of the factors analysis. Studies of the company technological maturity and possibility for implementing business processes and certain IT technologies have become more advanced in some degree. The general idea of forming a model of diagnostics of the management and technological maturity is based on the determination of prevailing company system influence components. Management techniques are a nucleus of the model, and the innovation level of management techniques is an energy impulse inciting to development. Basing on the analysis performed, the author created a concept of levels of the company management and technological maturity considering the main parameters of the company management and technological maturity. A composite algorithm was proposed for determining the level of managerial technological maturity (LMTM), end exposition of a complex of management techniques to ensure the company dynamic progress based on determining a level of the management and technological maturity. The advantages and disadvantages are determined by the methodology. The performed approbation has confirmed the approach validity and its usefulness. The approbation shows the reliability and unambiguity of interpreting results. To use it for bigger enterprises and corporations, it is not even necessary to change identification parameters.